As funções éticas da imaginação - Otero, Marcela (Universidade do Vale do Rio dos Sinos, 2018)
This study aims to analyze the connection between ethics and imagination from the perspective of Paul Ricoeur. It was sought to emphasize in this research the ethical aspects of its hermeneutic phenomenology in relation to the imagination, to the ethical exercise of distance, as well as to the ethical bias of the poetic dimension and narrative identity. In addition, it was also sought to clarify ethical issues of the social imaginary by addressing the themes of ideology and utopia. At the end of the study one can say that it is possible to understand that Ricoeur relates ethics to the construction of human identity, as capable of constructing a chain of conceptual and social meanings about his own life. In conclusion, the importance of understanding the hermeneutics of Paul Ricoeur's action is demonstrated by means of a self that is able to think and narrate its own history and to modify itself through imagination.
As funções éticas da imaginação
Keywords: Imaginação; Ética; Ricoeur; Imagination; Ethic; Ricoeur; ACCNPQ::Ciências Humanas::Filosofia